2023
DOI: 10.3389/fmars.2023.1230896
|View full text |Cite
|
Sign up to set email alerts
|

First estimates of population size and home range of Caribbean reef and nurse sharks using photo-identification and BRUVS

Johanna Kohler,
Mauvis Gore,
Rupert Ormond
et al.

Abstract: The assessment of parameters population size and individual home range is important for effective conservation management of sharks. This study uses the novel application of photo identification (photo-ID) to BRUVS footage as a non-invasive alternative to tagging in order to generate individual capture histories. These were used in mark-recapture models to estimate effective population sizes and to determine home ranges. In the Cayman Islands a total of 499 shark sightings of six coastal shark species were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 129 publications
2
6
0
Order By: Relevance
“…While a suggested year-around presence of Caribbean reef sharks in the Cayman Islands was found, this study also demonstrated that individual Caribbean reef sharks exhibit occasional long-distance (> 100 km) movements and across deep (up to 2,000 m) water. These long-distance movements by some sharks between the different Cayman Islands were also evident from parallel work using photo-identification of individuals recorded on BRUVS [22]. Large scale movements (> 100 km) have been observed for other reef-associated species including grey reef shark (250 km [86], 134 km: [53]), blacktip reef shark (138 km: [88]) and bull shark (Carcharhinus leucas) (650 km: [49], 2,000 km [89]) and some studies suggested that Caribbean reef sharks might also be more dispersive than previously thought [11,23].…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…While a suggested year-around presence of Caribbean reef sharks in the Cayman Islands was found, this study also demonstrated that individual Caribbean reef sharks exhibit occasional long-distance (> 100 km) movements and across deep (up to 2,000 m) water. These long-distance movements by some sharks between the different Cayman Islands were also evident from parallel work using photo-identification of individuals recorded on BRUVS [22]. Large scale movements (> 100 km) have been observed for other reef-associated species including grey reef shark (250 km [86], 134 km: [53]), blacktip reef shark (138 km: [88]) and bull shark (Carcharhinus leucas) (650 km: [49], 2,000 km [89]) and some studies suggested that Caribbean reef sharks might also be more dispersive than previously thought [11,23].…”
Section: Discussionmentioning
confidence: 67%
“…Evidence from previous acoustic telemetry studies suggests that Caribbean reef sharks are highly resident and exhibit strong site-fidelity to particular areas [2,[18][19][20][21]. Other recent data suggest that this species may be more mobile and dispersive than previously thought [2,20,22], with individuals undertaking excursions far beyond the typical, relatively small linear home range (< 20 km) and including occasional long-distance movements (>50 km) across open water [11,23,24] up to 700 m deep [25]. Furthermore, this species may play an important role in habitat linkages through both diel and ontogenetic habitat shifts, moving from shallower to deeper water between night and day and with increasing individual size [26][27][28].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…As a result, knowledge of the biology and demography of sharks is often limited. To overcome some of these challenges, the use of photographic identification (photo‐ID) can provide non‐invasive and affordable solutions that enable individual recognition based on distinctive natural markings captured on photographs or video cameras (Anderson et al, 2011; Kohler et al, 2023; Marshall & Pierce, 2012; Pierce et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Using either a combination of identification features or only one feature, the use of photo‐ID can provide insights into how populations change at the level of individuals: photo‐ID has been used to study the spatial movement patterns of grey nurse sharks, Carcharias taurus (Barker & Williamson, 2010); Caribbean reef sharks, Carcharhinus perezi ; nurse sharks, Ginglymostoma cirratum (Kohler et al, 2023); sevengill sharks, Notorynchus cepedianus Lewis et al, 2020); and whale sharks, Rhincodon typus (Holmberg et al, 2009). Photo‐ID also enabled estimates of population demography using capture‐mark‐recapture (CMR) analyses (also known as photographic mark‐recapture; Meekan et al, 2006; Dudgeon et al, 2008; Towner et al, 2013; Andreotti et al, 2016; Gore et al, 2016).…”
Section: Introductionmentioning
confidence: 99%